Sulfur-containing epoxy compound as well as preparation method and application thereof

By catalyzing the condensation reaction of epoxy chloride and trimercaptothiol, sulfur-containing epoxy compounds are prepared as optical material monomers, combining toughening agents and curing agents to form high-performance epoxy resin optical materials, solving the problems of high cost, complex process and insufficient optical performance of epoxy resin in the prior art, and achieving a combination of high mechanical properties and excellent optical properties.

CN119751383AInactive Publication Date: 2025-04-04JIANGSU SHIKE NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411922769.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing epoxy resin optical materials have problems such as high cost, complex process and insufficient optical performance, which are difficult to meet the needs of high-end optical applications.

Method used

By catalyzing the condensation reaction of epoxychlorohydrin and trimercaptothiol, a ring-opening sulfide ether is formed, and then the ring is closed under the action of a strong alkali to obtain a sulfur-containing epoxy compound. This method is used to prepare optical material monomers, combining toughening agents and curing agents to form high-performance epoxy resin optical materials through polymerization.

Benefits of technology

It achieves the improvement of optical performance while maintaining high mechanical properties, with high visible light transmission, refractive index and low yellow index, which is suitable for the production of high-end optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751383A_ABST
    Figure CN119751383A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-containing epoxy compound as well as a preparation method and application thereof. The method comprises the following steps: synthesizing a sulfur-containing epoxy compound as shown in a formula a, catalyzing epoxy chloropropane and trimercaptothiol to carry out condensation reaction to generate ring-opening thioether, and then removing hydrogen chloride to carry out ring closing to finally obtain the sulfur-containing epoxy compound. The sulfur-containing epoxy compound prepared according to the method has excellent optical properties on the premise of maintaining mechanical properties such as high hardness, high wear resistance and impact resistance, and the visible light transmittance is greater than or equal to 89%, the refractive index is greater than or equal to 1.59, and the yellow index is less than or equal to 1.20. The composite material is suitable for manufacturing optical components with high requirements on optical and mechanical properties, such as optical lenses, mobile phone protection screens and computer protection screens, and a wider material selection range is provided for application of high-end optical components. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical materials, and in particular relates to a sulfur-containing epoxy compound optical material and a preparation method thereof. Background Art

[0002] As a kind of special optical material of high molecular polymer, optical grade epoxy resin plays a vital role in related fields. From coatings, optical instruments, optical protection in daily life to optical fiber communication and laser technology in high-tech fields, they are inseparable from high-performance epoxy resin optical materials. In electronic devices such as smartphones and tablets, high-resolution display screens require the use of high-quality optical materials to improve image clarity and color protection; in optical instruments, high-quality epoxy resin optical materials can improve imaging quality and observation effects, etc.

[0003] Existing epoxy resin synthesis methods mainly include the following two:

[0004] Synthesis of bisphenol A type epoxy resin: One-step method: add bisphenol A, epichlorohydrin and sodium hydroxide to the reaction system at the same time. The reaction conditions of this method are difficult to control, because epichlorohydrin is prone to hydrolysis and other side reactions, and the performance indicators of the product such as the epoxy value are not very stable, but the production process is simple and the equipment utilization rate is high. Two-step method: The first step is that bisphenol A reacts with epichlorohydrin under the action of a catalyst (quaternary ammonium salt) to generate chlorohydrin ether; the second step is that the chlorohydrin ether reacts with sodium hydroxide to dehydrochlorinate and form an epoxy group to obtain an epoxy resin. The epoxy resin obtained by this method has stable quality, high epoxy value, and high product purity, but there are many production steps and high cost.

[0005] Synthesis of aliphatic epoxy resin: Using aliphatic olefin cyclopentadiene as raw material, epoxidation reaction is carried out with peroxy acid. The epoxy resin produced by this method has good flexibility and is widely used in coatings and other fields.

[0006] In summary, the traditional epoxy resin has problems such as high cost and complex process. On the other hand, its optical performance needs to be further improved to meet the needs of higher-end optical applications. In this context, by optimizing and improving the synthesis technology of epoxy compounds, developing new sulfur-containing epoxy compound monomer materials, and providing better solutions for optical applications in various fields, it has important strategic significance and social value. Summary of the invention

[0007] In view of the above-mentioned problems in the prior art, the present invention provides a sulfur-containing epoxy compound and a preparation method and application thereof. By catalyzing epichlorohydrin and trithiothiol to carry out a condensation reaction, an open-ring thioether is generated, and then the hydrogen chloride is removed to close the ring, and finally a sulfur-containing epoxy compound is obtained. The sulfur-containing epoxy compound prepared according to the method is used as a monomer for preparing optical materials. On the premise of maintaining mechanical properties such as high hardness, high wear resistance and impact resistance, it has excellent optical properties, among which the visible light transmittance is ≥89%, the refractive index is ≥1.59, and the yellowness index is ≤1.20. It is suitable for making optical components with high requirements for optical and mechanical properties, such as optical lenses, mobile phone protective screens and computer protective screens, etc., providing a wider range of material selection for the application of high-end optical components.

[0008] To achieve the above object, the present invention includes the following technical solutions:

[0009] A sulfur-containing epoxy compound, the structure of which is shown in formula a:

[0010]

[0011] On the other hand, the present invention provides a method for preparing the sulfur-containing epoxy compound as described above, the method comprising the following steps:

[0012] Epichlorohydrin and 1,3,5-trimercaptomethylbenzenethiol are added to a reaction container containing methanol, and a sodium hydroxide aqueous solution with a concentration of 6-10 wt% is added dropwise with stirring, and the reaction is carried out at a temperature of 0-15° C. for 6-10 hours, wherein the weight ratio of epichlorohydrin, trimercaptomethylbenzenethiol and sodium oxide solution is (25-60): (30-70): (3-10); 30-40 wt% sodium hydroxide aqueous solution is continuously added dropwise, the temperature is raised to 25-35° C., the addition is stopped after precipitation occurs, and the reaction is carried out for 1-3 hours; chloroform and water are added to extract the organic layer, and the organic layer is eluted and rotary evaporated to obtain a colorless and transparent sulfur-containing epoxy compound (a).

[0013] In the method for preparing the sulfur-containing epoxy compound as described above, preferably, the amount of methanol added is 1.6 to 6 times the weight of epichlorohydrin.

[0014] Epichlorohydrin and polythiothiols undergo condensation reaction under alkaline conditions. Epichlorohydrin opens the ring and reacts with the thiol group. The thiol forms a sulfur anion, which attacks the epoxy three-membered ring to generate an open-ring thioether, which then closes the ring under the action of a strong base to generate a triepoxide compound. The product liquid is mostly soluble in the chloroform layer and is obtained by separation extraction. Sodium chloride is discharged with the water.

[0015] The specific reaction formula is as follows:

[0016]

[0017] In yet another aspect, the present invention provides use of the sulfur-containing epoxy compound as described above as an optical material.

[0018] In the application as described above, preferably, the optical material is an optical lens, a mobile phone protective screen or a computer protective screen.

[0019] In another aspect, the present invention provides an epoxy resin optical material, which is prepared by polymerizing the sulfur-containing epoxy compound as described above.

[0020] In another aspect, the present invention provides a method for preparing the epoxy resin optical material as described above, the method comprising the following steps:

[0021] (1) adding a toughening agent and a curing agent into a reactor containing a sulfur-containing epoxy compound (a), and stirring to form a prepolymer, wherein the weight ratio of the toughening agent, the curing agent and the sulfur-containing epoxy compound (a) is (0.5-3): (60-100): (80-150);

[0022] (2) The prepolymer is vacuum-defoamed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 35-45°C for curing for 1-5 hours, then heated to 45-60°C for curing for 1-5 hours. After naturally cooling to room temperature, the prepolymer is demolded and sampled to obtain an epoxy resin optical material.

[0023] In the method for preparing the epoxy resin optical material as described above, preferably, the step (1) further comprises adding a colorant, a catalyst, a diluent, a release agent and / or a light absorber.

[0024] Beneficial effects of the present invention:

[0025] First, in terms of the optical properties of the material, the sulfur-containing epoxy compound (a) has a higher visible light transmittance and refractive index and a lower yellowness index, which ensures its use as an optical window material and makes the invented product have a wider range of applications.

[0026] Secondly, in terms of material mechanical properties, the optical material prepared from the sulfur-containing epoxy compound (a) has high strength, surface hardness and toughness, and can effectively resist deformation and cracking when subjected to external forces, thereby improving the reliability of optical components.

[0027] In addition, the preparation process of the present invention is relatively simple, easy to operate and control, and through reasonable adjustment of process parameters, precise regulation of optical material properties can be achieved, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the infrared spectrum of the sulfur-containing epoxy compound (a) prepared in Example 1.

[0029] Figure 2This is the HNMR nuclear magnetic resonance hydrogen spectrum of the sulfur-containing epoxy compound (a) prepared in Example 1. DETAILED DESCRIPTION

[0030] The present invention is further described below by means of specific examples, but this is not intended to limit the protection scope of the present invention.

[0031] Example 1: Preparation of sulfur-containing epoxy compound (a)

[0032] 450g of epichlorohydrin and 500g of 1,3,5-trimercaptomethylbenzenethiol were added to a reaction vessel containing 1200g of methanol, and the mixture was stirred for 50 minutes and dripped. 90g of 9% sodium hydroxide solution was added and reacted at 10°C for 6.5 hours. 36% sodium hydroxide aqueous solution was added at the same rate, and the temperature was raised to 30°C. After 47 minutes, a precipitate appeared, and the addition was stopped. The reaction was continued for 1.5 hours. Chloroform and water were added to extract the organic layer, and the organic layer was eluted and rotary evaporated to obtain 462g of colorless and transparent epoxy compound (a). The yield was 82.2%.

[0033] Infrared spectrum FT-IR test: The product prepared in Example 1 (i) was subjected to Fourier transform infrared spectrum FT-IR) test. Figure 1 The analysis of the middle curve shows that 3048.5cm- 1 The absorption peak at 2915.9cm- is the stretching vibration of the CH of the benzene ring. 1 , 2970.9cm- 1 The absorption peak at 2500 cm-1 is the stretching vibration of methylene CH. The characteristic absorption peak of the SH bond of the reactant at around 2500 cm-1 completely disappears. 1 , 837.4cm- 1 The absorption peak at is the symmetric stretching vibration of the epoxy ring.

[0034] H NMR nuclear magnetic resonance hydrogen spectrum analysis: Figure 2 As shown. δ = 2.50-2.62ppm corresponds to the two hydrogen atoms on the methylene group in the epoxy ring of the compound, δ = 2.75-2.79ppm is the two hydrogen atoms on the methylene group connected to the epoxy ring, the sulfur atom cannot rotate freely in the molecule, and the chemical shifts of the two hydrogen atoms in the methylene group are not equivalent, δ = 3.07-3.12ppm corresponds to one hydrogen on the methine in the epoxy ring, δ = 3.74-3.83ppm corresponds to two hydrogen atoms on the methylene group connected to the benzene ring, which is affected by the end group of the epoxy ring and presents multiple peaks, δ = 7.21ppm corresponds to one hydrogen connected to the benzene ring, and there is no hydrogen atom on the adjacent carbon, so it presents a single peak.

[0035] Example 2: Preparation of epoxy resin optical sheet

[0036] (1) Add 2.5 g of propylene glycol toughening agent and 180 g of isophorone diamine curing agent into a reactor containing 210 g of the sulfur-containing epoxy compound (a) prepared in Example 1, and stir at a low speed to form a prepolymer.

[0037] (2) The prepolymer is vacuum-defoamed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing oven, heated to 40°C for curing for 2 hours, then heated to 50°C for curing for 3.5 hours. After naturally cooling to room temperature, the prepolymer is demolded and sampled to obtain an epoxy resin optical sheet with a thickness of 2 mm.

[0038] Comparative Example 1:

[0039] Comparative Example 1 adopts the same preparation conditions as Example 2, except that the sulfur-containing epoxy compound (a) is replaced by a commercially available epoxy resin monomer raw material. The specific raw materials are shown in Table 1.

[0040] Table 1 Comparison of comparative samples prepared under the same formulation conditions

[0041]

[0042] Example 3: Optical performance testing experiment on epoxy resin polymer optical material

[0043] The optical properties of the epoxy resin polymer optical materials prepared in Examples 1-2 and Comparative Example 1 were tested respectively. Transmittance is one of the most important properties of optical materials, which is expressed by transmittance. The UV-8000 ultraviolet visible photometer of Shanghai Yuanxi Instrument Co., Ltd. was used for the test. The test method was: directly place the sample on the ultraviolet visible photometer to measure the transmittance; the refractive index test was performed using the WZS1 Abbe refractometer of Shanghai Optical Instrument Equipment Co., Ltd. The test method was: place the prepared epoxy resin optical material sample on the prism of the Abbe refractometer to measure the refractive index; the yellow performance test was based on the GB / T 2409-80 standard. The test method was: use a colorimeter to directly read the X, Y, and Z values, and calculate the value by the formula YI = (1.28X-1.06Z) × 100÷Y. The test results are shown in Table 2.

[0044] Table 2 Comparison of optical properties of prepared substrate samples

[0045]

[0046] It can be seen from the results in Table 2 that the optical sheet prepared from the sulfur-containing epoxy compound of the present application has a higher visible light transmittance and refractive index, and a lower yellowness index.

[0047] Example 4: Testing the wear resistance and impact strength of epoxy resin polymer optical materials

[0048] The epoxy resin polymer optical materials prepared in Example 2 and Comparative Example 1 were tested for wear resistance and impact strength. Surface wear resistance test: The surface wear resistance of the polymer resin sample is expressed by the haze value. According to the reference standard GB 10810.5-2012, the sample to be tested is placed on a haze meter and rubbed back and forth with steel wool to measure the difference between the initial haze value of the central area of ​​the sample before friction and the haze value after friction; the impact strength meter is the highest steel ball mass without cracks, for example, a 90g steel ball impacts three times, the material has no cracks, and a 100g steel ball impacts cracks, then the impact strength of this material is 90g. Test method: A substrate with a thickness of 2.0mm is fixed at the bottom of the instrument, and steel balls of different masses (80g, 90g, 100g) are selected and vertically and freely dropped from a height of 1.30m to the center of the surface of the substrate material in turn. Each mass of the steel ball is measured three times. The test results are shown in Table 3.

[0049] Table 3 Mechanical properties of prepared substrate samples

[0050]

Claims

1. A sulfur-containing epoxy compound, characterized in that Its structure is shown in formula a:

2. The method for preparing a sulfur-containing epoxy compound according to claim 1, characterized in that: The method comprises the following steps: Epichlorohydrin and 1,3,5-trimercaptomethylbenzenethiol are added to a reaction container containing methanol, and a 6-10 wt% sodium hydroxide aqueous solution is added dropwise with stirring, and the mixture is reacted for 6-10 hours at a temperature of 0-15° C., wherein the weight ratio of epichlorohydrin, trimercaptomethylbenzenethiol and sodium oxide solution is (25-60):(30-70):(3-10); 30-40 wt% sodium hydroxide aqueous solution is added dropwise, the temperature is raised to 25-35° C., the addition is stopped after precipitation occurs, and the mixture is reacted for 1-3 hours; chloroform and water are added to extract the organic layer, and the organic layer is eluted and rotary evaporated to obtain a colorless and transparent sulfur-containing epoxy compound (a).

3. The method for preparing a sulfur-containing epoxy compound according to claim 2, characterized in that: The amount of methanol added is 1.6 to 6 times the weight of epichlorohydrin.

4. Use of the sulfur-containing epoxy compound as claimed in claim 1 as an optical material.

5. The use according to claim 4, characterized in that: The optical material is an optical lens, a mobile phone protective screen or a computer protective screen.

6. An epoxy resin optical material, characterized in that: The material is prepared by polymerizing the sulfur-containing epoxy compound described in claim 1.

7. The method for preparing the epoxy resin optical material according to claim 6, characterized in that: The method comprises the following steps: (1) adding a toughening agent and a curing agent into a reactor containing a sulfur-containing epoxy compound (a), and stirring the mixture to form a prepolymer, wherein the weight ratio of the toughening agent, the curing agent and the sulfur-containing epoxy compound (a) is (0.5-3):(60-100):(80-150); (2) The prepolymer is vacuum-defoamed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 35-45°C for curing for 1-5 hours, then heated to 45-60°C for curing for 1-5 hours. After naturally cooling to room temperature, the prepolymer is demolded and sampled to obtain an epoxy resin optical material.

8. The method for preparing an epoxy resin optical material according to claim 6, wherein: The step (1) further comprises adding a toner, a catalyst, a diluent, a release agent and / or a light absorber.

Citation Information

Patent Citations

  • Optical resin monomer with high refractive index and preparation method thereof

    CN102329298A

  • Method for preparing thioepoxy-based optical material and polymerizable composition thereof

    CN104053657A

  • Sulfur-containing epoxy resin monomer and optical resin material and preparation methods thereof

    CN106279289A

  • Stable, aqueous epoxy resin dispersion, process for its preparation, and its use

    CN1122348A